A Retrospective Assessment of Pediatric Dental Trauma Patients Before and During the COVID-19 Outbreak - Sera Şimşek Derelioğlu; Fatih Şengül; Nilay Öztürk Heikholaemeh; Periş Çelikel (Atatürk University, 2024)
Objective: The aim of this study was to compare the number of patients admitted to the Department of Pediatric Dentistry at Atatürk University Faculty of Dentistry in 2020 due to dental trauma with the previous year, and to determine the causes and forms of trauma during the pandemic). Methods: In this retrospective study, dental trauma records were evaluated. The number of patients admitted, their age, sex, type of trauma, location of the trauma, and the affected teeth were analyzed. The distribution of trauma cases over the years in terms of sex, dentition, jaw, and location was evaluated using Chi-square analysis. Results: The incidence of dental trauma among the patients who visited our clinic in 2019 and 2020 was 0.35% and 0.83%, respectively. Enamel-dentin fractures from dental hard tissue injuries were the most common type of trauma in both years. No statistically significant differences were found in the distribution of trauma cases by year in terms of sex, dentition, jaw, and location (p>0.05). Conclusion: The COVID-19 outbreak led to a reduction in dental trauma cases. However, it is noteworthy that dental traumas occurred more frequently in outdoor environments, despite restrictions on children going out due to the pandemic. Since no significant reduction in the frequency of dental traumas was observed during the COVID-19 outbreak in children, it is important to inform parents and children about avoiding certain risky behaviors and protection methods.. Keywords: COVID-19 outbreak, Pediatric dentistry, Dental trauma Pediatrik Diş Travması Hastalarının COVİD-19 Salgını Öncesi ve Sırasında Retrospektif Olarak Değerlendirilmesi ÖZ Amaç: Bu çalışmanın amacı Atatürk Üniversitesi Diş Hekimliği Fakültesi Çocuk Diş Hekimliği Anabilim Dalı'na 2020 yılında diş travması nedeniyle başvuran hasta sayısını bir önceki yılla karşılaştırmak ve pandemi döneminde travmanın nedenlerini ve şekillerini belirlemektir. Yöntemler: Bu retrospektif çalışmada diş travma kayıtları değerlendirildi. Başvuru yapan hasta sayısı, yaşı, cinsiyeti, travma tipi, travmanın yeri ve etkilenen dişler analiz edildi. Travma olgularının yıllara göre cinsiyet, diş, çene ve lokasyona göre dağılımı Ki-kare analizi kullanılarak değerlendirildi. Bulgular: Kliniğimize 2019 ve 2020 yıllarında başvuran hastalarda diş travması görülme sıklığı sırasıyla %0,35 ve %0,83 idi. Diş sert doku yaralanmalarına bağlı mine-dentin kırıkları her iki yılda da en sık görülen travma tipiydi. Travma olgularının yıllara göre cinsiyet, diş yapısı, çene ve lokasyona göre dağılımında istatistiksel olarak anlamlı farklılık saptanmadı (p>0,05). Sonuç: COVİD-19 salgını diş travması vakalarında azalmaya neden olmuştur. Ancak pandemi nedeniyle çocukların dışarı çıkması kısıtlanmasına rağmen diş travmalarının dış ortamlarda daha sık meydana geldiği dikkat çekiyor. Çocuklarda COVİD-19 salgını sırasında diş travmalarının sıklığında anlamlı bir azalma görülmediğinden, ebeveynlerin ve çocukların bazı riskli davranışlardan kaçınma ve korunma yöntemleri konusunda bilgilendirilmesi önemlidir. Anahtar Kelimeler : COVID-19 salgını, Çocuk diş hekimliği, Diş travması